DFT simulation-based screening of single transition metals supported on g-C3N4 for the catalytic oxidation of Hg0. (1st December 2021) - Liu, Shuai; Xu, Mengxia; Chen, Yipei; Yu, Jiahui; Pang, Chengheng; Wu, Tao
Graphical abstract: Highlights: Breaking energy of Metal-O on g-C3 N4 supported VIIIB group metals were studied. Oxygen molecules are more favorably adsorbed on the metal active sites than Hg 0. The oxidation involves O2 dissociation, metal-O bond breakage and HgO desorption. Strong metal-O bond was indicated by electronic structure and partial bader charge. Ni shows potential in Hg oxidation due to its low energy barrier for HgO desorption. Abstract: In this study, the adsorption and oxidation of elemental mercury by O2 on a series of buckled g -C3 N4 monolayer-supported transition metals were investigated using Density Functional Theory method. It is shown that O2 molecules are adsorbed more strongly on the active sites compared with Hg 0 atoms, while the catalytic oxidation of Hg 0 undergoes three key steps, i.e., O2 dissociation, metal-O bonds cleavage and HgO desorption. Results also demonstrated that for the dissociation of O2, the energy barrier is inversely proportional to the adsorption energy of O atom. Among the catalysts studied, Fe- g -C3 N4 exhibits the lowest energy barrier (0.44 eV) for O2 dissociation. The Pd- g- C3 N4 is found as the most efficient catalyst for the cleavage of the first and second Pd-O bonds with an external energy of 1.28 and 2.03 eV, respectively. The covalent interaction of metal-O bonds is demonstrated by the overlaps between metal d orbitals and O p orbitals. DFT calculations also show that HgO desorption plays a crucial role in the oxidation process, which requires up to 2.92 eV for the desorption of the first HgO on the Pd- g- C3 N4 . The rate-determining step for the oxidation of mercury on Fe, Co, Pt and Rh- g- C3 N4 is the cleavage of the second metal-O bonds, which has an energy barrier greater than 2.90 eV, while for the Pd- g- C3 N4, the mercury oxidation process is dominated by the desorption of the first HgO. However, for the Ni- g -C3 N4, it is limited by the reaction between O2 * and the first Hg 0 with an energy barrier of 2.59 eV. Therefore, it can be concluded that the Ni- g- C3 N4 is of the greatest potential to be used as the catalyst for the catalytic oxidation of Hg 0 by O2 atmosphere.